Analisis dan Desain Analisis dan Desain Sistem Informasi Laboratorium di Lingkungan Politeknik Negeri Madura: Mengoptimalkan Efisiensi dan Akurasi Proses Pengelolaan Data - A Labib Fardany Faisal; Aries Alfian Prasetyo; Ahmad Mustafa Mustofa; Ahmad Afandi (Techno Bahari, 2023)
An efficient and accurate laboratory information system has a very important role in supporting scientific research and development activities. In this study, the analysis and design of laboratory information systems were carried out to optimize efficiency and accuracy in data management in the laboratory environment. The approach used includes analyzing user needs, evaluating existing systems, identifying data needs, analyzing security and privacy, and designing system architecture, databases, user interfaces, and workflows. Through user needs analysis, we understood the challenges faced by the laboratory in data management and determined the functional and non-functional needs of the laboratory information system. Evaluation of the existing system helped us identify the weaknesses and strengths of the system in use, which then formed the basis for improvements and changes. Identification of data needs involves recognizing the types of data generated and managed by the laboratory, as well as the necessary integration of data between systems. Security and privacy analysis provides an understanding of the data security needs in the laboratory environment, and measures to mitigate security risks are proposed. The system architecture design includes the network infrastructure, servers, and hardware required to support the laboratory information system. Database design considers the optimal database structure for storing and managing laboratory data with attention to normalization, data integrity, and system performance. An intuitive and easy-to-use user interface is designed so that users can efficiently access and manipulate laboratory data. Workflow design ensured that the data management process in the laboratory was well organized, and points of automation and integration with other laboratory tools or systems were identified to improve efficiency. Through the development of software applications in accordance with the system design, the laboratory information system can be implemented successfully. Testing and debugging are carried out to ensure the successful implementation of the system. With good implementation, laboratories can achieve increased productivity, accuracy, and security in their data management. This research provides a comprehensive framework for the analysis and design of laboratory information systems. The results of this research can provide long-term benefits for laboratories in improving the efficiency and accuracy of data management, which in turn will support scientific progress and research in various fields of science especially in Politeknik Negeri Madura.